DIMENSIUNEA SOCIO-CULTURALĂ A RELAŢIILOR MOLDOFRANCEZE ÎN CONTEXTUL PROCESULUI INTEGRAŢIONIST EUROPEAN - Cebotari, Svetlana; Cotilevici, Violeta (CEP USM, 2016)
The Moldovan-French cooperation is based on a document of a particular importance, the Treaty of understanding, friendship and cooperation between the Republic of Moldova and the French Republic. This act marks the traditional friendly relations community and the cultural and civilizational approximation between the French and Moldovan people. The legislation of the bilateral dialogue derives from the need to strengthen the European solidarity through the harmonization between states founded on the respect of the universal values of freedom, democracy and solidarity and on human rights respect. One year later, due to the signing on November 24, 1994 of the Agreement of cultural, scientific and technical cooperation between the Government of the Republic of Moldova and the Government of the French Republic, the Moldovan-French relations know are being strengthened on their socio-cultural dimension. The two governments from Paris and Chisinau decide to promote the cooperation between peoples of the two states in the field of culture, education, science, technology and training, taking into account cultural identities an economic needs of their countries, considering their common membership to the European cultural area and the participation in the development of projects of common interest in multilateral programs. By this act France is committed to support efforts manifested by the Republic of Moldova in favor of the French language.
Keywords: Moldovan-French relations; cultural and scientific cooperation; European area; Francophony; Moldovan-French associations; bilateral dialogue